Contemporary British Anarchism - Benjamin Franks; Ruth Kinna (Revue LISA)
This article outlines the principles which inform contemporary anarchist politics and approaches to anarchist ideology, identifies some of the activists who have had a significant influence on the broader movement and discusses a range of groups operating within it. It also looks at the ways in which anarchists organise and extend the influence of their ideas, considers paradigms for the evaluation of anarchist success and provides an extensive list of resources, as well as a bibliography.